The strategies, practice, and review you need for the score you want (New York, 2017)
THE PRINCETON REVIEW GETS RESULTS. Get all the prep you need for a perfect score on the Quantitative and Verbal sections of the GRE with 4 full-length practice tests, thorough GRE topic reviews, and extra practice online.
Keywords: Đại học và Cao đẳng,Universities and colleges; Kỳ thi,Công việc sau đại học,Examinations,Graduate work; Hoa Kỳ,United States